Optimasi Penempatan Recloser untuk Meningkatkan Keandalan Menggunakan Metode Virus Evolutionary Genetic Algorithm (VEGA) - Irawan, Novadianto Yudha; Amrita, Anak Agung Ngurah; Setiawan, Widyadi (Majalah Ilmiah Teknologi Elektro; Vol 17 No 2 (2018): (May - Agustus) Majalah Ilmiah Teknologi Elektro, 2018)
Kutampi Diesel Power Plant that supplies the Lembongan Island electrical system has a reliability value index that has not met the standard with SAIDI 95.85 hours / customer / year and SAIFI 76 times / customer / year while the WCS standard for SAIDI is 2.5 hours / customer / year and SAIFI is 3 times / customers / year. Reliability value can be improved one of them by adding recloser. The addition of the recloser should pay attention to the area of frequent interference, the percentage of load and impedance of the electricity system. The VEGA method was used to determine the optimal recloser location by minimizing the SAIDI and SAIFI values. The result of the optimization method using VEGA shows optimal recloser location in the group 5 with the highest fitness 8,8396 with SAIDI 0,0070 hour / customer / year and SAIFI 0,0061 times / customer / year with program running time ± 3,6 minutes. These values indicate the VEGA method is more accurate than the fuzzy and genetic algorithm combination method but requires a longer running time.